Do Pregnant Women Change Their Diet and Physical Activity After Gestational Diabetes Diagnosis? Findings from a Longitudinal Multi-racial U.S. Prospective Cohort (P16-016-19) - Hinkle, Stefanie (Curr Dev Nutr, 2019)
OBJECTIVES: Women diagnosed with gestational diabetes (GDM) are usually advised to reduce carbohydrate intake and increase physical activity (PA). There is limited longitudinal population-based evidence on whether these women change their diet and PA after diagnosis. Our aim was to examine if women with GDM do in fact alter their diet and PA post diagnosis and identify characteristics of women with favorable changes. METHODS: This study included 1735 women from the NICHD Fetal Growth Studies-Singletons (2009–2013) who completed an Automated Self-Administered 24-Hour dietary recall and a Pregnancy PA Questionnaire at 16–22, 24–29, 30–33, 34–37, and 38–41 (PA only) gestational weeks (GW). GDM was ascertained by medical records (n = 85; 4.9%), diagnosed at a mean of 27.7 GW (S.D. 4.7). We used adjusted linear mixed models with random effects to estimate changes in diet/PA post-GDM screening (non-GDM)/diagnosis (GDM) and tested for differences by GDM status. For factors that changed among women with GDM, we tested for differences by covariates. RESULTS: Women with GDM significantly reduced total sugar intake after diagnosis by 27.9 g/d (95% confidence interval −41.5, −14.3), while it increased in women without GDM by 3.7 g/d (0.7, 6.7) after screening (Figure). Specifically, women with GDM reduced added sugars [−12.0 g/d (−22.0, −2.0)] and fruit juice [−0.4 serving/d (−0.6, −0.2)], and increased artificially sweetened beverage intake [0.2 servings/d (0.1, 0.3)]. The significant reduction in total sugar persisted in all women except Hispanics [−9.0 g/d (−27.2, 9.3); P-interaction = 0.08] and non-nulliparous women [−10.7 g/d (−25.5, 4.2); P-interaction = 0.001]. Women with GDM performed less moderate intensity PA [−30.6 MET-hr/wk (−43.2, −18.0)] after diagnosis than before, which was less than women without GDM [−17.1 (−19.9, −14.3)]. CONCLUSIONS: Majority of women with GDM undergoing usual care substantially decreased their overall sugar intake after diagnosis primarily by reducing added sugars and fruit juice, and increasing artificially sweetened beverages. Greater dietary counseling efforts may be needed among Hispanic and multiparous women, and for PA in all women with GDM. FUNDING SOURCES: This research was supported by the Intramural Research Program of the Eunice Kennedy Shriver National Institute of Child Health and Human Development. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: